Vietnam : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This report provides the details of the IMF's projections and estimates of Vietnam on the summary of the tax systems; gross domestic product by expenditure categories; sector and ownership at current prices; gross domestic product by sector at constant prices during 1996-2002; consumer price inflation, 1999-2003; population and employment; gross value of industrial and agricultural production at constant prices; balance of payments during 1997-2002; summary of general government budgetary operations; government revenues and expenditures; exchange rate developments; treasury bills and bond issues during 1997-2003; summary of normal tariff schedule; common effective preferential tariff (CEPT) rates during 2000-03, and so on.